1982
DOI: 10.3382/ps.0610821
|View full text |Cite
|
Sign up to set email alerts
|

Curvilinear Trends in Direct and Some Correlated Responses to Nineteen Generations of Selection for Part Record Rate of Egg Production in a Randombred Line of Chickens

Abstract: Direct and correlated responses to 19 generations of selection for part record rate °f egg production were studied. The select line (B line) was derived from a base randombred control line (A line) which, in turn, was derived as a random sample of the Regional Cornell control population. Cumulative direct and correlated responses were computed as deviations of the generation means of the various traits from the corresponding means of the control line. Secondorder polynomial regressions of the various traits re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Hence the observed decline in rate of response for egg production in later periods may be attributed to decline in additive genetic variance ( Figure 2) rather than other factors. Whereas Yamada et al (1958) found the exhaustion of additive genetic variance as the main reason for cessation of response in their study, Ibe et al (1982) reported that large inbreeding effects were found to in uence the response to selection. Gowe and Fairfull (1985), though they did not nd a signi cant response to selection for egg production to 273 d in the last 10 generations, did not observe any signi cant decline in heritability/genetic variance of the trait.…”
Section: Discussionmentioning
confidence: 90%
“…Hence the observed decline in rate of response for egg production in later periods may be attributed to decline in additive genetic variance ( Figure 2) rather than other factors. Whereas Yamada et al (1958) found the exhaustion of additive genetic variance as the main reason for cessation of response in their study, Ibe et al (1982) reported that large inbreeding effects were found to in uence the response to selection. Gowe and Fairfull (1985), though they did not nd a signi cant response to selection for egg production to 273 d in the last 10 generations, did not observe any signi cant decline in heritability/genetic variance of the trait.…”
Section: Discussionmentioning
confidence: 90%
“…Selection for increased egg production in laying hens is generally based on cumulative part records (up to about 40 weeks of age) (SAADEH et al 1968;CRAIG et al 1969;KINNEY et al 1970;POGGENPOEL and ERASMUS 1978;GARWOOD and LOWE 1979;GARWOOD et al 1980;AYYAGARI et al 1980;IBE et al 1982;GOWE and FAIRFULL 1985;POGGENPOEL et al 1996). In general, the results indicated that selection for increased egg production based on part records led to increased rate of lay in the part record and to a positively correlated response in the full record.…”
Section: Introductionmentioning
confidence: 97%